CD8+-T Cells With Specificity for a Model Antigen in Cardiomyocytes Can Become Activated After Transverse Aortic Constriction but Do Not Accelerate Progression to Heart Failure - Gröschel, Carina; Sasse, André; Monecke, Sebastian; Röhrborn, Charlotte; Elsner, Leslie; Didié, Michael; Reupke, Verena; Bunt, Gertrude; Lichtman, Andrew H.; Toischer, Karl; Zimmermann, Wolfram-Hubertus; Hasenfuß, Gerd; et al. (Frontiers in Immunology, 2018)
Heart failure due to pressure overload is frequently associated with inflammation. In addition to inflammatory responses of the innate immune system, autoimmune reactions of the adaptive immune system appear to be triggered in subgroups of patients with heart failure as demonstrated by the presence of autoantibodies against myocardial antigens. Moreover, T cell-deficient and T cell-depleted mice have been reported to be protected from heart failure induced by transverse aortic constriction (TAC) and we have shown recently that CD4+-helper T cells with specificity for an antigen in cardiomyocytes accelerate TAC-induced heart failure. In this study, we set out to investigate the potential contribution of CD8+-cytotoxic T cells with specificity to a model antigen (ovalbumin, OVA) in cardiomyocytes to pressure overload-induced heart failure. In 78% of cMy-mOVA mice with cardiomyocyte-specific OVA expression, a low-grade OVA-specific cellular cytotoxicity was detected after TAC. Adoptive transfer of OVA-specific CD8+-T cells from T cell receptor transgenic OT-I mice before TAC did not increase the risk of OVA-specific autoimmunity in cMy-mOVA mice. After TAC, again 78% of the mice displayed an OVA-specific cytotoxicity with on average only a three-fold higher killing of OVA-expressing target cells. More CD8+ cells were present after TAC in the myocardium of cMy-mOVA mice with OT-I T cells (on average 17.5/mm2) than in mice that did not receive OVA-specific CD8+-T cells (3.6/mm2). However, the extent of fibrosis was similar in both groups. Functionally, as determined by echocardiography, the adoptive transfer of OVA-specific CD8+-T cells did not significantly accelerate the progression from hypertrophy to heart failure in cMy-mOVA mice. These findings argue therefore against a major impact of cytotoxic T cells with specificity for autoantigens of cardiomyocytes in pressure overload-induced heart failure.